2015
DOI: 10.2147/dmso.s79450
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled, clinical study on the effect of Diabetinol® on glycemic control of subjects with impaired fasting glucose

Abstract: BackgroundThis study investigated the efficacy of Diabetinol® in people with diabetes on medication but not meeting the American Association of Clinical Endocrinologists and American Diabetes Association glycemic, blood pressure, and lipid targets.Subjects and methodsFifty subjects, aged 18–75 years, with fasting blood glucose ≤15.4 mmol/L, hemoglobin A1c levels ≤12%, and a body mass index between 25 and 40 kg/m2, were enrolled in a 24-week, randomized, double-blind, placebo-controlled, parallel study. Diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Hence, there remains an urgent need for the development of effective and safe therapeutic agents. Citrus PMFs are attractive candidates due to their potent protective effects against MetS as well as safety in rodent experimental models ( 17 , 18 ). Here, we used an optimized and standardized method to purify PMFs from citrus peels based on macroporous resin chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there remains an urgent need for the development of effective and safe therapeutic agents. Citrus PMFs are attractive candidates due to their potent protective effects against MetS as well as safety in rodent experimental models ( 17 , 18 ). Here, we used an optimized and standardized method to purify PMFs from citrus peels based on macroporous resin chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…Given this promising data, there is room for the possible use of the nobiletin as a supplementation therapy for GDM in humans. Already, in non-pregnant humans, clinical trials have found that supplementation of either citrus flavonoids or Diabetinol ® (of which nobiletin is the primary active ingredient) has been found to significantly improve cardiometabolic parameters, including fasting glucose and lipid profiles [78,79]. In contrast, there remains a lack of clinical information on the effect of nobiletin supplementation on pregnancy and long-term offspring outcome.…”
Section: Discussionmentioning
confidence: 99%
“…NoT are flavonoids, a kind of polyphenol obtained from the rind of Citrus depressa, which is a type of lemon native to Okinawa in Japan, Taiwan, and China. For example, NoT has been reported to be effective for metabolic disorders [11] or memory impairment [12] as a dietary supplement, although it is not approved for medical use in clinics. From the perspective of chronobiology, a randomized clinical trial was conducted to evaluate the effectiveness and safety of NoT in patients with nocturia (NoT-nocturia study).…”
Section: Introductionmentioning
confidence: 99%